2017
DOI: 10.1088/1748-605x/aa5644
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparative assessment of decellularized bovine pericardial patches and commercial bioprosthetic heart valves

Abstract: Notwithstanding their wide exploitation, biological prosthetic heart valves are characterized by limited durability (10-15 years). The treatment of biological tissues with chemical crosslinking agents such as glutaraldehyde accounts for the enhanced risk of structural deterioration associated with the early failure of bioprosthetic valves. To overcome the shortcomings of the currently available solutions, adoption of decellularized biological tissues of animal origin has emerged as a promising approach. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…As we and other authors demonstrated [12][13][14][15][16], the decellularization of pericardium might be applied to produce biological scaffolds with improved immunocompatibility and unvaried biological and biomechanical properties with respect to native tissues. As an example, the clinical application of human acellular allogeneic pericardium as a patch during outflow tract reconstruction was effective in the midterm [17].…”
Section: Introductionmentioning
confidence: 75%
“…As we and other authors demonstrated [12][13][14][15][16], the decellularization of pericardium might be applied to produce biological scaffolds with improved immunocompatibility and unvaried biological and biomechanical properties with respect to native tissues. As an example, the clinical application of human acellular allogeneic pericardium as a patch during outflow tract reconstruction was effective in the midterm [17].…”
Section: Introductionmentioning
confidence: 75%
“…Another important feature of decellularization is the fact that it reduces antigenicity, especially of the xenografts . A range of protocols have been explored in decellularized BP using different substances, concentrations, and exposure times . Although many of these protocols were efficient in removing cell content, inadequate elimination of the xenoantigen alpha‐gal (Galα1‐3Galβ1‐(3)4GlcNAc‐R) was still a major obstacle .…”
Section: Introductionmentioning
confidence: 99%
“…In these protocols, pericardium is treated with hypotonic buffers and ionic or nonionic detergents, such as SDS and Triton X‐100 (Korossis et al, ; Mirsadraee et al, , ). Although these methods maintain a relatively good mechanical performance, abolish xenoantigen content (Boer et al, ; Gardin et al, ; Ghodsizad et al, ; Roosens et al, ; Wong, Wong, Athanasiou, & Griffiths, ), and reduce tissue immunogenicity (Aguiari et al, ; Wong, Wong, Vapniarsky, & Griffiths, ), thus far, there has been a limited employment of this approach at an industrial scale for preparation of valve replacement devices (Horke, ).…”
Section: Introductionmentioning
confidence: 99%